Intraparotid facial nerve schwannoma: a case report - Gibavičienė, Jolita; Čepulis, Vytautas (Acta medica Lituanica, 2013)
Background. Our objective is to present a very rare clinical case of intraparotid facial nerve schwannoma that clinically presented as an asymptomatic parotid tumor, mimicking pleomorphic adenoma, and was diagnosed only intraoperatively. Another purpose is to discuss diagnostic possibilities, appropriate planning for the management and predictive outcomes of surgical management. Materials and methods. A clinical case of a patient with an asymptomatic parotid mass diagnosed as a facial nerve schwannoma intraoperatively is presented. The patient’s presentation and the diagnostic procedures, surgery and the follow up procedures are discussed. A review of literature is presented. Conclusions. Intraparotid facial nerve schwannoma is an extremely rare entity and rarely diagnosed preoperatively. Management of intraparotid facial nerve schwannomas (IFNS) is very challenging because the diagnosis is often made intraoperatively and in most cases resection can lead to severe facial nerve (FN) paralysis with significant aesthetic consequences. Imaging studies and fine-needle aspiration cytology are not always helpful in preoperative diagnosis.
Keywords: parotid tumor; facial nerve schwannoma; facial paralysis